IMPLEMENTATION OF THE SNOWBALL THROWING MODEL TO INCREASE STUDENT LEARNING ACTIVENESS IN CLASS V PKN LEARNING IN KMB AT SDN 81 SIPATANA: Model Snowball Throwing - Fachrurrizal, Raja Nur Riza Yunita; Muda, Lisdawati; Iskandar, Karmila (STIT Pringsewu, 2024)
This research was motivated by the lack of student learning activeness in PKN learning material about Myself and My Environment. This research aims to determine the increase in learning activity of class V students at SDN 81 Sipatana during PKN learning. This type of research is Classroom Action Research (PTK). The subjects in this research were class V students at SDN 81 Sipatana, the number of students for the 2023-2024 academic year was 25 students consisting of 10 boys and 15 girls. This research was conducted in 2 cycles. Each cycle consists of 2 meetings and 4 stages which refers to the Kemmis and Taggart model which consists of 4 stages, namely: planning, action, observation and reflection. The results of this research indicate that implementing the Snowball Throwing Model can increase student activity in class V PKN learning in KMB at SDN 81 Sipatana. Data analysis in the research used descriptive percentage formulas for teacher activity, student activity and student activity. This can be seen from the increase in each cycle, namely cycle I obtained teacher activity 71.05%, student activity 73.52% and student activity 71.42% and increased in cycle II obtained teacher activity results 92.10%, student activity 91 .17% and student activity 91.07%. Based on the results of the research conducted, it can be concluded that implementing the Snowball Throwing Model can increase student activity in class V PKN learning in KMB at SDN 81 Sipatana.